A review on fatigue and rutting performance of asphalt mixes - Moghaddam, T.B.; Karim, M.R.; Abdelaziz, M. (2011)
Fatigue and rutting are very well known to be the two popular distresses that occur in road pavement. These are mainly due to the increase in the number of vehicles particularly those with high axle loads, due to the environmental conditions and also due to construction and design errors. As a consequence the service life of asphalt pavement is affected and will be decreased. Various researches reported that using additives such as different types of polymer and fiber in asphalt concrete (AC) could be a solution to postpone deterioration of AC pavement. This paper aims to highlight previous research works conducted on the effects of using different types of additives and aggregate gradation on fatigue and rutting resistance of AC mixtures. It was observed that fatigue and rutting resistance of AC mixture could be enhanced considerably by utilization of different types of additives such as fibers that can increase the amount of strain energy absorbed during fatigue and fracture process of the mix in the resulting composite. Also, fibers and polymers provide three-dimensional networking effect in asphalt concrete and stabilise the binder on surface of aggregate particles and prevent from any movement at higher temperature.